Hak Ulayat Laut dalam Perspektif Otonomi Daerah di Kepulauan Kei dan Papua - Roberth Kurniawan Ruslak Hammar (Fakultas Hukum Universitas Gadjah Mada, 2009)
Structure of customary right for land go out to sea as source of subsistence at society of Moluccas and Papua, existence still be confessed and adhered, goodness by citizen of federation punish, and also the foreigner, and if impinged to be sanctioned coherent. Autonomous execution of area hotly the reform and on the side of socialize, giving living space for execution of rights of customary right for land of deep sea construct reinforcement of rights socialize custom utilize to support area development.